2021
DOI: 10.1002/cbin.11585
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA‐1271‐5p regulates osteogenic differentiation of human bone marrow‐derived mesenchymal stem cells by targeting forkhead box O1 (FOXO1)

Abstract: Forkhead box O1 (FOXO1) is a key regulator of osteogenesis. The aim of this study was to identify the mechanisms of microRNAs (miRNAs) targeting FOXO1 in osteogenic differentiation of human bone marrow mesenchymal stem cells (hMSCs). Three miRNA target prediction programs were used to search for potential miRNAs that target FOXO1. Quantitative real‐time polymerase chain reaction was conducted to detect the expression of miR‐1271‐5p and FOXO1 during osteogenic differentiation. Target gene prediction and screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…The result showed that 13 miRNAs were remarkably highly expressed in PBMC of mice with osteoporosis. Among the 13 miRNAs, the expression trends of miR-1271-5p, miR-135a-5p, miR-135b-5p, miR-153-3p, miR-223-3p, miR-27a-3p, miR-370-3p, and miR-9-5p in the current study were in line with their trends in various studies [ 5 , 7 , 41 46 ]. Our result revealed that the expression of the 13 miRNAs was positively correlated with the progression of osteoporosis.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The result showed that 13 miRNAs were remarkably highly expressed in PBMC of mice with osteoporosis. Among the 13 miRNAs, the expression trends of miR-1271-5p, miR-135a-5p, miR-135b-5p, miR-153-3p, miR-223-3p, miR-27a-3p, miR-370-3p, and miR-9-5p in the current study were in line with their trends in various studies [ 5 , 7 , 41 46 ]. Our result revealed that the expression of the 13 miRNAs was positively correlated with the progression of osteoporosis.…”
Section: Discussionsupporting
confidence: 87%
“…As noncoding small RNAs, miRNAs can posttranscriptionally modulate the expression of specific genes, thus affecting various kinds of biological processes [4]. A number of studies on miRNAs affecting osteoporosis exhibited that miRNAs can regulate various genes and inhibit proliferation and differentiation of osteoblasts, thereby causing osteoporosis [5][6][7]. Meanwhile, works of literature also reported that predictive models for fracture risk due to osteoporosis can be constructed via miRNAs [8].…”
Section: Introductionmentioning
confidence: 99%
“…11 Stem Cells International NEDD4L as an E3 ubiquitin-protein ligase mediates ubiquitination modification to regulate the protein level 54], and our bioinformatics data suggested FOXA2 was a target of NEDD4L. FOX family members are essential for bone metabolism and function as regulators of OD of MSCs [28,[55][56][57]. FOXA2 is identified as a critical transcription factor involved in the process of MSCs in the repair of the injured pancreas, intestinal and hepatic tissues, and neurons [58][59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have indicated the importance of TWIST1 (Miraoui et al, 2010;Quarto et al, 2015;Fan et al, 2022) and LEP (Xu et al, 2016;Zhao et al, 2016) in the regulation of osteogenic differentiation: LEP reportedly alters the differentiation fate of chondrogenic progenitor cells and triggers their senescence (Zhao et al, 2016), and promotes osteoblast differentiation of BMSCs (Xu et al, 2016); meanwhile, inhibiting the expression of TWIST1 could promote the osteogenic differentiation of periodontal MSCs (Xu et al, 2019) and adipose tissue-derived stem cells (Quarto et al, 2015). FOXO1 transcription factor, a member of the Fox family, is mainly involved in cell proliferation, differentiation, angiogenesis and other biological processes, and multiple studies have also reported the involvement of FOXO1 during osteogenic differentiation (Hao et al, 2018;Chen et al, 2019;Yang et al, 2021). In our study, these four genes were all markedly up-regulated in osteogenic induction samples in comparison with uninduced hMSC samples, suggesting that they play vital roles in osteogenic differentiation of hMSCs, as reported in the above studies.…”
Section: Discussionmentioning
confidence: 99%